2018
DOI: 10.1002/jcb.26624
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription loop‐mediated isothermal amplification (RT‐LAMP), a light for mammalian transcript analysis in low‐input laboratories

Abstract: Transcript analysis is usually performed by costly, time-consuming, and expertise intensive methods, like real time-PCR, microarray, etc. However, they are not much feasible in low-input laboratories. Therefore, we implemented the reverse transcription loop-mediated isothermal amplification (RT-LAMP) as a means of mammalian transcript analysis. Particularly, RT-LAMP was developed for buffalo aromatase cytochrome P450 (CYP19) transcript, to study its expression in 3D-cultured buffalo granulosa cells, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In the present study, we did not observe any morphological difference in the shape and size of the spheroids between music treatment and control (Figure 1a,b). The typical spheroidal organization of the buffalo granulosa cells was similar to that of observed in our previous studies (Pandey et al, 2018; Yadav et al, 2018). The absence of the morphological difference between control and the treatment was also pronounced by a similar gene expression of the PCNA , a marker for cell proliferation, between control and music treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we did not observe any morphological difference in the shape and size of the spheroids between music treatment and control (Figure 1a,b). The typical spheroidal organization of the buffalo granulosa cells was similar to that of observed in our previous studies (Pandey et al, 2018; Yadav et al, 2018). The absence of the morphological difference between control and the treatment was also pronounced by a similar gene expression of the PCNA , a marker for cell proliferation, between control and music treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, there is a high probability that exposure to classic Vedic chants may influence the functions of the cultured cells. Therefore, we exposed 3D cultured buffalo granulosa cell spheroids, which have been established in our laboratory for mimicking preovulatory follicular stage (Pandey, Singh, & Onteru, 2018; Yadav, Agrawal, Pandey, Singh, & Onteru, 2018), to a classic Vedic chanting and studied the expression dynamics of steroidogenic genes in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is the first study to use AHR gene expression for milk dioxin detection through LAMP reaction, as the amplification products can be detected visually with the naked eye in normal white light. The RT-LAMP was standardized for the amplification of the AHR gene from granulosa cells spheroids by standardizing the concentration of template and primers at different temperatures and incubation time according to Pandey et al (2018). On the basis of colour detection with 120 nM Hydroxynaphthol blue (HNB) dye, all the RT-LAMP positive samples of the AHR gene from the granulosa cell spheroids of both the hanging drop and polyHEMA culture systems appeared blue in colour, whereas the non-amplified and non-template controls remained in violet colour (Figure 4 and Figure 5).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Therefore, the present work was focused on granulosa cells, considering them as the best representative of the reproductive toxicity by dioxins. In our previous study, we had developed CYP19-RT-LAMP assay for mammalian tanscript analysis in low-input laboratories (Pandey, et al , 2018) by using 3D cultured buffalo granulose spheroids treated with lipopolysaccharide (LPS). It is evident by several earlier studies that the LAMP technique was more specific and sensitive without the influence of other non-targeted nucleic acids and PCR inhibitors present in the tested samples, like blood and food materials.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been characterized by a few key GC transcript markers and estradiol production (Yadav et al, 2018). We utilized this 3D culture model system to investigate the effect of lipopolysaccharide (LPS) on CYP19 gene expression in buffalo GC (Pandey et al, 2018), and observed that LPS caused the downregulation in CYP19 transcript in in vitro as in in vivo conditions (Pandey et al, 2018). However, a comprehensive comparative transcriptome profile is not available among freshly isolated, 2D and 3D cultured buffalo GCs to understand the gene expression patterns in the in vitro culture systems.…”
Section: Introductionmentioning
confidence: 99%